2018
DOI: 10.3233/jad-170657
|View full text |Cite
|
Sign up to set email alerts
|

Caregiving and Caregiver Burden in Dementia Home Care: Results from the Prospective Dementia Registry (PRODEM) of the Austrian Alzheimer Society

Abstract: The findings are applicable to identify persons at risk for substantial CB and its consequences. There is demand for personal, psychological, and medical support of caregivers and increasing male participation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
73
1
4

Year Published

2018
2018
2029
2029

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(84 citation statements)
references
References 47 publications
6
73
1
4
Order By: Relevance
“…The three longitudinal studies all found that the duration of caregiving and the patient's functional status were the strongest determinants of burden (37)(38)(39). In every longitudinal study, caregiver burden increased non-linear over time since perceived burden increased at a steeper rate as time progressed.…”
Section: General Stressorsmentioning
confidence: 95%
“…The three longitudinal studies all found that the duration of caregiving and the patient's functional status were the strongest determinants of burden (37)(38)(39). In every longitudinal study, caregiver burden increased non-linear over time since perceived burden increased at a steeper rate as time progressed.…”
Section: General Stressorsmentioning
confidence: 95%
“…The diagnosis of dementia also has a high impact on the people with dementia, their families and caregivers (Alltag, Conrad, & Riedel‐Heller, ). The progressive loss of cognitive abilities and the behavioural and psychological symptoms of people with these neurodegenerative disorders can place many burdens on all parties involved (LoGiudice & Watson, ; Ransmayr et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Lorena Cortés | Laura Lacomba-Trejo | Marián Pérez-Marín Como se ha podido intuir, la situación de cuidado resulta en numerosas consecuencias personales, psicológicas, sociales, familiares y económicas para las personas cuidadoras a menudo invisibilizadas (De la Cuesta-Benjumea et al, 2018;Ransmayr et al, 2018).…”
Section: Intervención Profesionalunclassified
“…Se creó una entrevista semiestructurada de 55 preguntas, para llevar a cabo la presente investigación. La entrevista fue elaborada teniendo en cuenta las diferentes dimensiones propuestas en la literatura alrededor del cuidado informal y la perspectiva de género, a saber: perfil de las personas cuidadoras, impacto de los cuidados en la vida familiar, la estructura de género como proveedora de ayuda y apoyo en los cuidados, el rol tradicional de la mujer cuidadora, tareas domésticas y de cuidados ejercidas por mujeres, el trabajo de atención como un trabajo de género, aprendizaje de los cuidados, la voluntad de cuidar bien, compromiso, idoneidad del cuidado, las dificultades del cuidado, salud física y emocional de las cuidadoras, sobrecarga, estrés, impacto laboral del cuidado aislamiento social (Bremer et al, 2011;Casademont, 2018;Casaña-Granell et al, 2018;Cheix et al, 2015;Estrada et al, 2018;Fernández, 2018;LuÈdecke et al, 2018;Moral-Fernández et al, 2017;Peterson, 2015;Ransmayr et al, 2018;Tomás et al, 2019;Unson, Flynn, Haymes, Sancho, y Glendon, 2016;Valero-Moreno et al, 2018). Por lo tanto, las dimensiones de la entrevista y su contenido se pueden consultar en la Tabla 1.…”
Section: Medicionesunclassified
See 1 more Smart Citation